Expression of kawaii (‘cute’): gender reinforcement of young Japanese female school children - Asano-Cavanagh, Yuko (Australian Association for Research in Education (AARE), 2012)
This paper examines the Japanese word kawaii ‘cute’. Teachers frequently use kawaii to show positive feelings toward objects in the classroom. Female children also are primary users of the word, which suggests that they are acquiring kawaii as an index of female gender identity. From a linguistic perspective, kawaii is not lexicalised in other languages. While English speakers may say cute for various social actions, scholars suggest that kawaii is tied to empathy and relationships. Although the kawaii phenomenon has been discussed by many scholars, there has been no rigorous semantic analysis, particularly in its use by parents, students and teachers. The framework of the Natural Semantic Metalanguage (NSM) approach was applied to explicate the exact meaning of kawaii for non-Japanese speakers. The corpus was information about the paraphernalia provided for Japanese female students. The analysis indicates that the core meaning of kawaii is linked to a notion of a ‘child’, and the emotion is explained as ‘when I see this, I can’t not feel something good’. The kawaii syndrome reveals a Japanese cultural characteristic which puts much emphasis on being ‘gender appropriate’ in society and schools. The analysis has implications for understanding gender construction and expression in non-western cultures.